Orchid exploration in Tanjung Peropa Wildlife Reserves for Kendari Botanic Gardens collection, Indonesia - SRI HARTINI; POPI APRILIANTI (Society for Indonesian Biodiversity, 2020)
Abstract. Hartini S, Aprilianti P. 2020. Orchid exploration in Tanjung Peropa Wildlife Reserves for Kendari Botanic Gardens collection, Indonesia. Biodiversitas 21: 2244-2250. Tanjung Peropa Wildlife Reserve (Tanjung Peropa WR) is one of the conservation area in Southeast Sulawesi Province, Indonesia. The inventory of orchid in this area is still limited and Kendari Botanic Garden (Kendari BG) need to collect the orchids from this location. Orchid diversity inventory and exploration had been carried out on March 26- April 12, 2019, in Tanjung Peropa WR and collecting them as an ex-situ conservation effort in order to enrich Kendari BG plant collection. The specimen was collected by using explorative method at 5 locations in Tanjung Peropa WR. The result showed that there were 10 epiphytic orchids found of Aerides, Cymbidium, Dendrobium, Grammatophyllum, Liparis, Pomatocalpa, and Thrixspermum. Also, there were 5 terrestrial orchids of Corymborkis, Eulophia, Nervilia, Phaius, and Tropidia. The orchid species were found in the area between 25-110 m above sea level (asl), with temperature 27-31°C, humidity 75-80%, soil acidity 5.0-6.0, soil humidity 80-90%, and canopy dense between 60-80%. Kendari BG has collected 34 species of orchid from Southeast Sulawesi, with 25 species of epiphytic and 9 species of terrestrial orchids.